Designing Online Marketing Communication Programs To Improve Bling It On’s Instagram Using Benchmarking Method And Analytical Hierarchy Process (Ahp) Tool - Arinda Layla Alfira; Yati Rohayati; Ima Normalia Kusmayanti (eProceedings of Engineering, 2022)
AbstractBling It On is a local brand from Bandung that was founded in 2019. Bling It On focuses on selling various shoulder bags with unique and attractive models. For the last period, Bling It On’s income was unstable and did not reach the target, especially in online sales. One of the causes is low brand awareness of Bling It On due to less of Instagram optimization as the main platform in the marketing communication program. This research uses a benchmarking method through observations to identify gaps and find best practices from competitors' performance in Instagram. The Analytical Hierarchy Process (AHP) is also used as a decision-making tool to find the priority ranking on criteria (feed, story, profile, caption, reels) and the 16 Instagram sub criteria that are obtained from integration between VOC and previous research. From the results of this research, Bling It On is able to identify their weaknesses and design the appropriate strategies to improve Instagram performance by implementing the importance order of Instagram criteria and sub criteria. To overcome the shortcomings in the research, the researcher arranges implementation plans and work standards from the improvement design that have been validated by the problem owner.Keywords: Instagram, Online Marketing Communication, Benchmarking, Analytical Hierarchy Process, Fashion Brands